Aliansi Dalam Balancing: Analisis Normalisasi Hubungan Qatar Dengan Iran Ditengah Munculnya Pergeseran Aliansi Di Timur Tengah - rahma nia putri; Rajaa Yusuf Taufiqulhakim; Rike Alfiana; Siti Aisyah; Zaky Ismail (Politik Islam, 2024)
The need for regional alignments or alliances between large and small states has continued to influence international politics in recent decades. It has also given rise to the Gulf regional crisis which has largely become an increasingly important aspect of contemporary international political relations. The purpose of this article is to interrogate Iran-Qatar relations and the Gulf regional crisis, using the concept of balance of power as an analytical framework, and data from secondary sources. It argues that despite the economic blockade on Qatar, there has been improved relations between Qatar and Iran and more direct communication between officials of the two countries. However, the article concludes that the blockade imposed by the Gulf Cooperation Council (GCC) might further strengthen Iran-Qatar relations in the long run through the foreign policy taken by Qatar to normalise relations with Iran. This paper recommends that Qatar should constantly ensure proper manoeuvring between countries in the Gulf region for Qatar to survive and ensure its national interests are secured